Sebaran dan Keanekaragaman Cetacea saat Musim Timur di Perairan Tejakula, Buleleng, Bali - Andri Octapianus Purba; IGB Sila Dharma; Elok Faiqoh (Journal of Marine and Aquatic Sciences, 2020)
Cetaceans are marine mammals whose entire life is in marine and fresh waters. Cetaceans consist of whales, dolphins, and porpois. The distribution of cetaceans is a matter that shows the points of emergence of cetaceans in a waters. Diversity index is to determine the diversity of a group by looking at the number of species in a group. The waters of Tejakula Subdistrict are one of the waters in North Bali. The waters of North Bali is one of the waters which has become a migration path for several species of cetaceans. As a cetacean migration pathway, there are many occurrences of cetaceans in the northern waters of Bali. One of the most famous locations for the emergence of cetaceans in Bali is the waters of the Tejakula District, so research on cetaceans in the waters of the Tejakula Subdistrict needs to be done. This study aims to determine the distribution and diversity of cetaceans in the waters of Tejaula District. This research was conducted for 3 months, namely in the months of July, August and September 2017. Research on the distribution of cetaceans was carried out to determine the cetacean emergence points. The types of cetaceans found during the three months of the study were Stenella longirostris, Stenella attenuata, Globicephala macrorhynchus, Steno bredanensis, Lagenodelphis hosei, and Grampus griseus. The diversity of cetaceans in the waters of the Tejakula sub-district in July was 0.55, August 1.24 and September 0.9. The cetacea diversity index in the study area was divided into two, namely the area outside the reserve 1.22 and the area in the reserve 0.55.